Coordenação motora e leitura: a gênese de um jogo de tabuleiro para a Educação Física Escolar - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Our objective was to verify whether there is an association between the level of gross motor development and the reading performance of elementary school students in the early years. This study is of the type of association without interference between variables, conducted in a municipal school. It involved 188 students, aged between 9 and 11, of both genders, enrolled in the initial years (4th and 5th). The instruments used were the Motor Assessment Test Battery – KTK and the Reading Process Assessment Tests – PROLEC. The results demonstrated that 20% (38) of the participants had insufficient motor coordination; 23.5% (44) disturbance in motor coordination; 54.5% (102) normal coordination; and 2% (4) good cooperative. In grammatical structure, 91% (171) had normal performance and 9% (17) had difficulties; in Sentence Understanding, 74% (139) showed normal performance and 26% (49) had difficulties; in Text Comprehension 49% (92) showed “normal” performance; 51% (96) difficulties. The inferential analysis did not detect media associations and large magnitudes between the variables studied, therefore the hypothesis of our study was not confirmed. We emphasize, however, the need to investigate possible associations with the other variables that make up the reading process
Keywords: Desempenho psicomotor; Psicomotricidade; Capacidade motora em crianças; CIENCIAS SOCIAIS APLICADAS; Avaliação Motora; Desempenho Escolar; Desempenho Motor; Ensino Fundamental; Educação Física Escolar; Amazônia